Learner Autonomy in L2 Writing: The Role of Academic Self-Concept and Academic Achievement. (26th November 2021) - Tajmirriahi, Tayebeh; Rezvani, Ehsan
Abstract : Embracing a learner-based approach in line with a psychological perspective, the present study investigates learner autonomy (LA) in L2 writing with a focus on the role of academic self-concept (ASC) and academic achievement of Iranian English-as-a-Foreign-Language (EFL) university students. The research entailed three interrelated phases: In phase one, the readiness of 69 EFL students in three intact English essay writing classes was measured in terms of certain factors of autonomy in writing. Besides, their ASC was surveyed and the participants were asked to report their overall grade point average (GPA) as an index of their academic achievement. In phase two, a focus group interview was administered. Three emergent themes were derived from their comments, namely, insignificant position of writing, insufficient strategy use, and instructors' unconvincing support for autonomy in writing. The last phase of the study was assigning the findings of phase one to several regression and correlation analyses to investigate the triangular potential relationships of LA in writing, ASC, and academic achievement. The results of the study indicated that, compared with skills and strategy use, EFL university students were most autonomous in their attitudes towards writing, while they did not show a desirable level of ASC. Moreover, ASC and LA in writing proved to have a relatively significant relationship; nonetheless, academic achievement turned out insignificant in relation to them, proving no triangular correlation among the given variables. Implications for EFL teachers and materials developers focused on writing skill will be provided.